Cetak Biru Arsitektur Web-GIS untuk Pemetaan dan Klasifikasi Warisan Budaya Multi-Kategori di Kota Bandung Menggunakan Pendekatan Waterfall - Farly Mochamad (Departement Information Systems Universitas Kebangsaan Republik Indonesia, 2026)
This study aims to design a blueprint for a web-based geographic information system (Web-GIS) architecture specifically designed for mapping and classifying high-intensity cultural heritage in Bandung City. Although Bandung has a very high number of heritage assets, its operational data remains fragmented, statistical, and textually protected across various scattered sources, which hinders real-time monitoring and increases structural vulnerability amidst rapid urban development. This study uses a descriptive method with a structural system design approach, requirements implementation analysis and system design phases of the Waterfall model based on the Pressman software engineering paradigm. The technical design uses Data Flow Diagrams (DFDs) and Entity Relationship Diagrams (ERDs) to organize a new multi-category data synchronization scheme in accordance with local regulations (Categories A, B, and C). The output of this study is a robust system architecture, database model, and user interface design validated through empirical alignment with the city registry and field observations. Initial testing of the interactive prototype, which included Black Box Testing across fifteen functional scenarios and a System Usability Scale (SUS) assessment involving five respondents, resulted in a 100% functional consistency rate and an average SUS score of 78.5 (“Acceptable”), indicating favorable initial usability. Rather than developing a fully operational Web-GIS platform, this study presents a validated architectural blueprint and interactive prototype that provide the technical basis for future full-scale operational implementation, deployment, and evaluation.